Mental Health Challenges In the Educational Landscape of Serbia: Exploring Academic and Legal Perspectives - Škobo, Milena (Medicine, Law & Society, 2024)
This research paper investigates the mental health challenges faced by teachers in Serbia, emphasizing both educational and legal perspectives in the post-pandemic and AI-driven era. Recognizing teachers as vital contributors to human capital and societal progress, the study aims to shed light on the pressing concerns impacting their well-being. By exploring evidence-based practices, the research seeks to contribute to policy recommendations that foster a supportive work environment, acknowledging the integral role of teacher mental health in shaping a successful education system and positively influencing student well-being as they enter theworkforce.